Bifurkasi pada Model Predator-Prey Diskret dengan Fungsi Respon Ratio-Depedent dan Pemanenan - Agus Suryanto; Vira Hari Krisnawati; Sri Puji Lestari; Denis Andre Matatula; Mohammad Fahrurrozy (Limits: Journal of Mathematics and Its Applications, 2025)
This article discusses a predator-prey model with a ratio-dependent functional response and harvesting in both populations.  The differential equation of predator-prey model is discretized using the Euler method. The dynamics of the obtained discrete time model are investigated by determining the fixed points as well as their stability properties, and bifurcation analysis. Bifurcation analysis shows that the discrete time model can experience bifurcation, both period-doubling bifurcation and Neimark-Sacker bifurcation, when the value of time-integration step  passes a critical value. The analysis results have been confirmed by our numerical simulation results presented at the end of this article.